2005
DOI: 10.1007/s11240-004-3016-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in vitro bulblet regeneration from immature embryos of endangered Sternbergia fischeriana

Abstract: Sternbergia fischeriana is an endangered geophyte and therefore in vitro micropropagation of this plant will have great importance for germplasm conservation and commercial production. Bulb scale and immature embryo explants of S. fischeriana were cultured on different nutrient media supplemented with various concentrations of plant growth regulators. Immature embryos produced higher number of bulblets than bulb scales. Large numbers of bulblets were regenerated (over 80 bulblets/explants) from immature embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 25 publications
7
32
0
3
Order By: Relevance
“…Bulb scales are most commonly used as explants for in vitro micropropagation of geophytes. earlier studies regarding shoot and bulblet multiplication in geophytes indicated that addition of growth regulators to basal media promoted bulblet regeneration from bulb scales of many geophytes (6,9,17,19). BAP and KIN also generally increased the bulblet formation in our study.…”
Section: Tablesupporting
confidence: 78%
See 1 more Smart Citation
“…Bulb scales are most commonly used as explants for in vitro micropropagation of geophytes. earlier studies regarding shoot and bulblet multiplication in geophytes indicated that addition of growth regulators to basal media promoted bulblet regeneration from bulb scales of many geophytes (6,9,17,19). BAP and KIN also generally increased the bulblet formation in our study.…”
Section: Tablesupporting
confidence: 78%
“…It can be said that KIN and BAP were more inductive for bulblet production than TDZ and 2-iP. In general, addition of TDZ and 2-iP to the media reduced the bulblet regeneration frequency as previously described in Sternbergia fischeriana (6). A superiority of BAP and KIN was reported in different explants of geophytes species (3,5,6,15).…”
Section: Tablesupporting
confidence: 64%
“…Acclimatization of in vitro regenerated bulblets is the most challenging task due to smaller size and dormancy found in the in vitro regenerated bulblets (Mirici et al, 2005;Petric et al, 2011). Therefore, optimum bulblet size with adequate rooting is a prerequisite for successful acclimatization.…”
mentioning
confidence: 99%
“…Aerial segments of plants (leaf, pedicle, sepal, petal, ovary, embryo anther) and undergrounds organs (tuber, bulb, rhizome, corm and tuberous root) were used as explant in tissue culture of geophytes (Kim and De Hertogh, 1997). The most commonly used explant for micropropagation of geophytes are bulb scales (Mirici et al, 2005). The greatest problem in tissue culture of underground organs like bulb scales is the high percentage of contamination, which can result in a significant loss of cultures during the in vitro period (Kim and De Hertogh, 1997 (George, 1993;Reed et al, 1998;Leifert, 2000).…”
Section: Approaches To Enhance Lily Bulblet Growth In Vitromentioning
confidence: 99%
“…Studies on different stages of storage organ formation, induction, initiation and growth of storage organs (De Hertogh and Le Nard, 1993;Sarkar, 2008), can be considered on the morphological, physiological, biochemical and molecular level (Podwyszynska, 2012). Bulb scales are the main explants used in tissue culture of bulbous crops (Mirici et al, 2005). Many valuable bulbous crops like lily (Varshney et al, 2000;Skorić et al, 2014), amaryllis (Ilczuk et al, 2005), hyacinths (Yi et al, 2002) and daffodils (Santos and Salema, 2000) In Chapter 3, we examined lily bulblet growth and regeneration percentage in different lily explants including, petiole, leaves and scale explants.…”
mentioning
confidence: 99%